The Riemann homogeneous boundary value problem in the class of analytic functions with the given indicator under the entire order - Alehno, A. G. (Mathematical Modelling and Analysis, 1998)
The Riemann homogeneous boundary value problem is investigated in the class of piecewise analytic functions. The necessary and sufficient conditions are obtained for the existence of the solution. First Published Online: 14 Oct 2010